2014
DOI: 10.3758/s13415-014-0303-x
|View full text |Cite
|
Sign up to set email alerts
|

Emotion-induced blindness reflects competition at early and late processing stages: An ERP study

Abstract: Emotion-induced blindness (EIB) refers to impaired awareness of items appearing soon after an irrelevant, emotionally arousing stimulus. Superficially, EIB appears to be similar to the attentional blink (AB), a failure to report a target that closely follows another relevant target. Previous studies of AB using event-related potentials suggest that the AB results from interference with selection (N2 component) and consolidation (P3b component) of the second target into working memory. The present study applied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
68
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(84 citation statements)
references
References 41 publications
13
68
1
2
Order By: Relevance
“…Specifically, in contrast to studies demonstrating that emotional stimuli capture attention to their location, in EIB target perception is worse at the location of the emotional distractor (e.g., Most & Wang 2011). This pattern has led to suggestions that emotional distractors compete for neural representation with targets that appear in the same receptive field (Wang et al 2012; also see Keysers & Perrett 2002), a suggestion consistent with findings that neural responses to targets and emotional distractors exhibit a trading relationship (Kennedy et al 2014). Because people tend to prioritize emotional information, it is the emotional distractors that win, an effect that seems to be modulated by mood (Most et al 2010).…”
Section: Representation Of Affect In Sensory Cortexmentioning
confidence: 55%
“…Specifically, in contrast to studies demonstrating that emotional stimuli capture attention to their location, in EIB target perception is worse at the location of the emotional distractor (e.g., Most & Wang 2011). This pattern has led to suggestions that emotional distractors compete for neural representation with targets that appear in the same receptive field (Wang et al 2012; also see Keysers & Perrett 2002), a suggestion consistent with findings that neural responses to targets and emotional distractors exhibit a trading relationship (Kennedy et al 2014). Because people tend to prioritize emotional information, it is the emotional distractors that win, an effect that seems to be modulated by mood (Most et al 2010).…”
Section: Representation Of Affect In Sensory Cortexmentioning
confidence: 55%
“…One participant was excluded from the analyses because he reported ignoring the spatial cue in the cued-attention task. This sample size was chosen on the basis of previous studies probing similar effects of diffuse-attention manipulations (Arend et al, 2006;Olivers & Nieuwenhuis, 2006;Wierda et al, 2010) and previous studies of the EAB (Kennedy, Rawding, Most, & Hoffman, 2014;Most et al, 2005;Most et al, 2007;Smith, Most, Newsome, & Zald, 2006), ranging from 11 to 24 participants.…”
Section: Participantsmentioning
confidence: 99%
“…Recently, in an EEG ERP study, Kennedy et al (2014) showed that EIB shows the same ERP markers as AB, suggesting that the mechanisms involved in AB and EIB are similar. They call for further investigations to show that these overlaps indicate that both AB and EIB are very similar mechanism.…”
Section: Discussionmentioning
confidence: 99%